Emergencies in public law the legal politics of containment - Loevy, Karin (New York, NY Cambridge University Press, 2016)
"Debates about emergency powers traditionally focus on whether law can or should constrain officials in emergencies. Emergencies in Public Law moves beyond this narrow lens, focusing instead on how law structures the response to emergencies and what kind of legal and political dynamics this relation gives rise to. Drawing on empirical studies from a variety of emergencies, institutional actors, and jurisdictional scales (terrorist threats, natural disasters, economic crises, and more), this book provides a framework for understanding emergencies as long-term processes rather than ad hoc events, and as opportunities for legal and institutional productivity rather than occasions for the suspension of law and the centralization of response powers"-- Provided by publisher.
Introduction : after exception -- Part I : Theories of containment -- An introduction to the background theoretical problem : the paradox and its paradigmatic solutions -- The legacy of the models in the legal politics of emergnecies -- Part II : Practices of containment -- The legal politics of definitions : Article 15 derogations in the House of Lords -- The legal politics of authorization : the office of legal counsel (OLC) in the U.S. Executive and the Joint Committee on Human Rights (JCHR) in the U.K. Parliament -- The legal polities of jurisdiction : regional intervention in a domestic disaster, Cyclon Nargis in 2008 -- The legal politics of time and temporality : ticking time in the Israeli Supreme Court -- Part III : consequences of containment -- The legal politics of change and continuity in emergencies -- Horizons of containment : a dialectical process story of emergencies and change -- Epilogue : the process of emergency.
Keywords: Emergency management -- Law and legislation; Electronic books